2017
DOI: 10.1186/s12891-017-1853-1
|View full text |Cite
|
Sign up to set email alerts
|

Neck-specific exercises with internet-based support compared to neck-specific exercises at a physiotherapy clinic for chronic whiplash-associated disorders: study protocol of a randomized controlled multicentre trial

Abstract: BackgroundGlobally, neck pain is the fourth most common condition associated with longer periods of living with disability. Annually, approximately 0.3% of the population of Western countries undergo whiplash trauma, and half of those individuals will develop chronic problems with high costs for the individual and society. Evidence for chronic whiplash-associated disorders (WAD) treatment is scarce, though neck-specific training at a physiotherapy clinic twice a week for 12 weeks has demonstrated good results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 101 publications
0
25
0
Order By: Relevance
“…The projects, include experimental sub-group trials, each independent of the others, but using the same cohort to obtain data, in a prospective, multicentre, randomized controlled trial (RCT) with two parallel treatment arms conducted in outpatient care in Sweden according to a protocol established before recruitment started. (For further information, please see ClinicalTrials.gov Protocol ID: NCT03022812 and Peolsson et al [24]) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The projects, include experimental sub-group trials, each independent of the others, but using the same cohort to obtain data, in a prospective, multicentre, randomized controlled trial (RCT) with two parallel treatment arms conducted in outpatient care in Sweden according to a protocol established before recruitment started. (For further information, please see ClinicalTrials.gov Protocol ID: NCT03022812 and Peolsson et al [24]) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Arranging an appointment for a physical examination and an additional interview for the present sub-group study is set up as the last step to ensure that the criteria for study participation are met. If all the study criteria are met, and written and oral informed consent are confirmed, the patient will complete a written questionnaire and have physical measurements taken of neck-related functions [24]. Baseline measurements must be completed for inclusion [24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were recruited from an ongoing randomized controlled trial [23] evaluating two different ways of distributing neck-speci c exercises to individuals with chronic WAD Grade II and III [24] in primary health care in Sweden. Those who had completed at least half of the training sessions and the 1-year follow-up were eligible to participate in the present study.…”
Section: Setting and Participantsmentioning
confidence: 99%